La frontera como factor de integración regional. Análisis a partir del caso de la frontera entre Colombia y Perú - Londoño Niño, Edgar Andrés (2015)
This paper aims to highlight the importance of the border in the regional integration processes, with the case of the border between Colombia and Peru, to demonstrate the relevance to understanding the border such an integration element between neighboring states. First, the paper develops a discussion about the origin and understanding of the concept of border. In the second part, the difference between boundary and frontier are analyzed, and, in the third part, is highlighted the border´s importance such integration component and the elements that support and justify this focus. With the case of the border between Colombia and Peru, the paper highlights that the negative understanding of the border must be overcome for an understanding that consider the common factors and the necessity of cooperation and integration processes between neighboringcountries for the regional development and the welfare of the inhabitants.